2021
DOI: 10.1111/jocn.15763
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of urinary tract infections in hospitalised patients with spinal cord injury

Abstract: Aims and objectives: To investigate the incidence of urinary tract infection and analyse its risk factors among hospitalised patients with spinal cord injury.Background: While the incidence of urinary tract infection varies widely according to the healthcare setting and patients' clinical characteristics, formal reports are limited in quantity. There has been no consensus regarding the risk factors for urinary tract infection.Design: A retrospective descriptive study.Methods: Electronic medical records of 964 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Additionally, we conducted a stratified analysis based on sex, revealing that males exhibited a prolonged duration of indwelling catheters compared to females across all identified UTI risk factors. A Korean study also suggests that this may be a result of sex being associated with a higher percentage of male patients having indwelling catheters than female patients, instead of a correlation between UTI and sex 15 . There are significant sex-stratified differences in bladder management after SCI, which should be noted by healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we conducted a stratified analysis based on sex, revealing that males exhibited a prolonged duration of indwelling catheters compared to females across all identified UTI risk factors. A Korean study also suggests that this may be a result of sex being associated with a higher percentage of male patients having indwelling catheters than female patients, instead of a correlation between UTI and sex 15 . There are significant sex-stratified differences in bladder management after SCI, which should be noted by healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance and urological care are vital for sexually active individuals. Those prone to UTIs should be advised promptly on preventive measures, including safe sexual practices and hygiene maintenance [23,24]. When UTI symptoms manifest, children aged 12-14 have a 1.9-fold higher risk of bacterial UTIs, and those aged 14-18 have a 3.2fold higher risk compared to younger children (6-12 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Renal failure is the primary cause of late death in patients with SCIs. [41][42][43] Therefore, scientific bladder management and training important for reducing urinary complications and improving the quality of life of patients with SCIs. This study showed that the number of micturition, residual urine volume, and LUTS score in the comprehensive care group were significantly lower than those in the general care group, and maximum urine and bladder volumes in the comprehensive care group were significantly higher than those in the general care group, suggesting that comprehensive functional nursing can promote the recovery of bladder function in patients with SCI.…”
Section: Discussionmentioning
confidence: 99%